Pengaruh Employee Relations terhadap Motivasi Kerja Karyawan PT. Joop Fine Interiors - Boby Hermawan Arifin (Jurnal Spektrum Komunikasi, 2020)
This study uses the theory of the Strategic Employee Communication Model for variable X, and uses the theory of factors that influence motivation from Khomsarial Romli. This research uses a quantitative approach and explanative research type. The population in this study were 55 employees of PT Joop Fine Interiors using census sampling technique. The data collection technique used in this study was a questionnaire, then the respondents' answers were processed using a Likert scale and the data analysis technique used was simple linear regression analysis with the help of SPSS version 20 for Windows. The conclusion of this study on the employee relations variable the majority of respondents answered strongly agree and agree with a total score of 2,946 with a mean of 4.12. On the employee work motivation variable, the majority of respondents answered strongly agree and agree with a total score of 3,207 and a mean of 4.16. The next conclusion, this study proves the influence of employee relations on employee motivation at PT Joop Fine Interiors. The results of this study indicate that employee relations has a positive effect on employee motivation at PT Joop Fine Interiors. This can be seen from the results of the simple linear regression test on the coefficient of determination is 0.462 which indicates that employee relations has a strong effect, amounting to 46.2% of the work motivation of PT Joop Fine Interiors employees and the remaining 53.8% is influenced by other factors outside this research. Based on the hypothesis test, this study proves that there is a significant influence with tcount> ttable (6,745.2007), so Ho is rejected and Ha is accepted, which means that the regression coefficient is significant, that is, there is an effect of employee relations on employee motivation at PT. Joop Fine Interiors.